Asthma and Inhaled Corticosteroid Effect on the Dental Arch Morphology in Children - Abdul Wadood, Meena O.; A. Al-Dahan, Zainab A. (Journal of Baghdad College of Dentistry, 2016)
Background: asthma has an influence on craniofacial development. Recently evidences show that there is an association between oral health problems and chronic lung disease. The present study was designed to estimate the changes in arch dimension measurements among asthmatic children aged 12 years old who were collected from AL- Zahra Center Advisory for Allergy and Asthma and compare them with the non-asthmatic children of the same age and gender. Material and Methods: Fifty children (25 asthmatic and 25 non- asthmatic children) were included for the odontometric measurement. For both upper and lower study models, photographs were taken using special photographic apparatus for each child, and the statistical analysis were done by using SPSS version 19. For permanent dentition, two liner measurements were utilized for each dental arch including width and length. Results: The results of the current research revealed that the mean values of dental arch dimensions, width and length; for both maxillary and mandibular dental arches among asthmatic children were lower as compared to non- asthmatic children in both genders. Conclusions: The findings of the present study showed that asthma and inhalation treatment in asthmatic children played an important role to minimize odontometric measurement including dental arch dimensions.